Effect of ionizing radiation on rat parotid gland - Boraks,George (2008)
A common side effect of radiotherapy used in the treatment of oral cancer is the occurrence of structural and physiological alterations of the salivary glands due to exposure to ionizing radiation, as demonstrated by conditions such as decreased salivary flow. The present study evaluated ultrastructural alterations in the parotid glands of rats receiving a fractionated dose (1,500-cGy) of radiation emitted by a Cesium-137 source and rats that were not subjected to ionizing radiation. After sacrifice, the parotid glands were removed and examined by transmission electron microscopy. Damage such as cytoplasmic vacuolization, dilatation of the endoplasmic reticulum and destruction of mitochondria, as well as damage to the cellular membrane of acinar cells, were observed. These findings lead to the conclusion that ionizing radiation promotes alterations in the glandular parenchyma, and that these alterations are directly related to the dose level of absorbed radiation. Certain phenomena that appear in the cytoplasm and nuclear material indicate that ionizing radiation causes acinar cell death (apoptosis).